Efficacy of a high quality O1/Campos foot-and-mouth disease vaccine upon challenge with a heterologous Korean O Mya98 lineage virus in pigs - Galdo Novo, Sabrina (2018)
In 2010 serotype O foot-and-mouth disease virus of the Mya98 lineage/SEA topotype spread into most East Asian countries. During 2010–2011 it was responsible for major outbreaks in the Republic of Korea where a monovalent O/Manisa vaccine (belonging to the ME-SA topotype) was applied to help control the outbreaks. Subsequently, all susceptible animals were vaccinated every 6 months with a vaccine containing the O/Manisa antigen. Despite vaccination, the disease re-occurred in 2014 and afterwards almost annually. This study focuses on the in vivo efficacy in pigs of a high quality monovalent commercial O1/Campos vaccine against heterologous challenge with a representative 2015 isolate from the Jincheon Province of the Republic of Korea. Initially, viral characterizations and r1 determinations were performed on six viruses recovered in that region during 2014–2015, centering on their relationship with the well characterized and widely available O1/Campos vaccine strain. Genetic and antigenic analysis indicated a close similarity among 2014–2015 Korean isolates and with the previous 2010 virus, with distinct differences with the O1/Campos strain. Virus neutralisation tests using O1/Campos cattle and pig post vaccination sera and recent Korean outbreak viruses predicted acceptable cross-protection after a single vaccination, as indicated by r1 values, and in pigs, by expectancy of protection. In agreement with the in vitro estimates, in vivo challenge with a selected field isolate indicated that O1/Campos primo vaccinated pigs were protected, resulting in a PD50 value of nearly 10. The results indicated that good quality oil vaccines containing the O1/Campos strain can successfully be used against isolates belonging to the O Mya98/SEA topotype.